Pengaruh Host dan Minat Menonton - Amelia, Theodora; Yoedtadi, Moehammad Gafar (Koneksi, 2024)
The Family 100 program hosted by Irfan Hakim at MNCTV station has been able to survive in prime time since its inception. This study wants to determine the effect of host Irfan Hakim on interest in watching Family 100 on Instagram followers @family100id. The research approach used is quantitative. The data collection method of this research is a survey and literature study. The population of this study were followers of the @family100id Instagram account. Data collection was carried out with a simple random sampling survey. The results of simple linear regression testing show that host Irfan Hakim has a positive influence on the interest in watching Instagram followers @family100id. However, the Adjusted R Square value (coefficient of determination) of 0.178 or 17.8% is obtained from the results of the coefficient of determination analysis and shows that the variable influence of host Irfan Hakim tends to have little impact on the variable interest in watching Instagram followers @family100id. This is due to the varied preferences of the audience, including other factors that influence it. Program Family 100 yang dipandu oleh Irfan Hakim di stasiun MNCTV mampu bertahan di waktu utama (prime time) sejak awal penayangan. Penelitian ini ingin mengetahui pengaruh host Irfan Hakim terhadap minat menonton Family 100 pada followers Instagram @family100id. Pendekatan penelitian yang digunakan adalah kuantitatif. Metode pengambilan data penelitian ini adalah survei dan studi kepustakaan. Populasi penelitian ini adalah followers akun Instagram @family100id. Pengambilan data dilakukan dengan survei simple random sampling. Hasil pengujian regresi linear sederhana menunjukkan bahwa host Irfan Hakim membawa pengaruh positif terhadap minat menonton followers Instagram @family100id. Namun, Nilai Adjusted R Square (koefisien determinasi) sebesar 0,178 atau 17,8% diperoleh dari hasil analisis koefisien determinasi dan menunjukkan bahwa variabel pengaruh host Irfan Hakim cenderung berdampak kecil terhadap variabel minat menonton followers Instagram @family100id. Hal tersebut disebabkan preferensi penonton yang bervariasi termasuk faktor lain yang turut berpengaruh.